A Prediction Equation for Day Night Wind Ratio Correction on Reference Crop Evapotranspiration - Rao, G Ramakrishna; Tate, S L; Varade, S B (Annals of Arid Zone, 2016)
Tht' reference crop evapotranspiration predicted by Modified. Penman may have limitation in using the results in water requirement studies of crops, if day and night lime weather data adjustment is not made. Therefore, a regression equation of the form ETo = 0.969 +0.812 ETo* for applying day night wind ratio correction on the not adjusted reference crop evapotranspiration predicted by modified Penman is suggested. The correlation coefficient (r) between the not adjusted evapotranspiration (ETo*) and adjusted evapotranspiration (ETo) is 0.96. The standard error (Sb) of the estimated evapotranspiration from the equation is 0.024, the 't' test value of the estimate is 35.53 which is found to be highly significant at 5% and 1% levels.